Prevalence of non-adequate health literacy in Europe: a systematic review and meta-analysis. (13th November 2019) - Baccolini, V; Di Paolo, C; Salerno, C; Rosso, A; Prencipe, G P; Isonne, C; Marzuillo, C; De Vito, C; Villari, P; Romano, F
Abstract: Background: Many studies show that a low level of health literacy (HL) is associated with several adverse outcomes. The aim of this systematic review was to estimate the prevalence of non-adequate HL (NAHL) in European countries and outline the main needs for interventions. Methods: The systematic search was performed in April 2019 and updated in June 2019. PubMed, Embase and Scopus were searched. Articles were considered eligible if they were cross-sectional studies published in English after 2000 and estimating the NAHL prevalence in European countries. Globally, 15490 articles were retrieved. Adapted Newcastle-Ottawa Scale was applied for the quality assessment. Several stratified meta-analyses were carried out. We also performed a meta-regression analysis to test the association between variables and NAHL. Results: In total, 59 articles of heterogeneous quality were included, providing data for 98 studies to include in the proportion meta-analysis. Overall, quantitative analysis yielded a pooled NAHL prevalence of 40% (95%CI, 36%-43%). Despite the prevalence varied considerably by country, it seemed to follow a geographic gradient, with the northern countries clearly having a lower prevalence than the other European counterparts. The pooled prevalence estimates (PEs) varied significantly according to the different type of HL assessment method applied. Also, high study quality was found to be significantly associated with a reduction of NAHL in the PEs. Grouping the sample in general population, oncology patients, chronic disease patients and refugees, the meta-regression analysis showed a significantly lower prevalence of NAHL in oncology patients. Conclusions: Although the PEs varied in relation to several factors (e.g. either among population groups, or depending on the HL assessment method), this study shows that more than one in every three surveyed participants had NAHL. Targeted strategies and coordinated policies aiming at improving HL in the Region are needed. Key messages: Despite several variations, a significant proportion of European population has non-adequate health literacy. Targeted public health strategies of intervention are crucial to address this deficit.